A qualitative study of barriers to innovation in academic libraries in Taiwan. Issue 6 (31st May 2019) - Chuang, Fu-Hsuan; Weng, Hui-Chuan; Hsieh, Pao-Nuan
Abstract : Purpose: The purpose of this paper is to explore innovation barriers in academic libraries. Through analysis of barriers to innovation, the authors can further elucidate the nature of innovation in academic library settings, which can help remove factors that hamper innovation. Design/methodology/approach: Using a qualitative case study to explore the innovation processes for two academic libraries, this study includes interviews with 28 interviewees, from senior leadership positions to practical librarians, to analyze the barriers to innovation they have experienced. Findings: Building on a literature review, this study proposes a barrier to innovation framework for academic libraries. The qualitative findings identified two specific barrier types that academic libraries face, environmental and organizational barriers, identifying 19 barrier factors that intertwine to yield seven dimensions across the two levels of analysis. It is advised that library leadership team should both encourage innovative behaviors and eliminate the innovation barriers to enhance library innovation capacities. Originality/value: The insights from this study can help the library managers of academic libraries to develop preemptive actions for dealing with various barrier scenarios, and thereby enhance possibilities of successful innovations.